Otitis media. (June 2012) - Cunningham, Michael; Guardiani, Elizabeth; Kim, Hung Jeffrey; Brook, Itzhak
Otitis media represents a broad spectrum of disease, which include acute otitis media and otitis media with effusion. As immunization with the pneumococcal conjugate vaccine has become more widespread, the microbiological landscape of otitis media has changed, which affects the treatment options facing clinicians worldwide. This review discusses the diagnosis and medical management of acute and chronic suppurative otitis media, the changes noted over the past decade, and briefly expounds on the surgical management of their severe complications.